2001
DOI: 10.37236/1595
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Hankel Matrices in Coding Theory and Combinatorics

Abstract: Hankel matrices consisting of Catalan numbers have been analyzed by various authors. Desainte-Catherine and Viennot found their determinant to be $\prod_{1 \leq i \leq j \leq k} {{i+j+2n}\over {i+j}}$ and related them to the Bender - Knuth conjecture. The similar determinant formula $\prod_{1 \leq i \leq j \leq k} {{i+j-1+2n}\over {i+j-1}}$ can be shown to hold for Hankel matrices whose entries are successive middle binomial coefficients ${{2m+1} \choose m}$. Generalizing the Catalan numbers in a different dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 63 publications
1
39
0
Order By: Relevance
“…. } (they coincide with the polynomials defined in (1.8) in [26]). Taking into account (57) and (58), to prove Lemma 24 it is then sufficient to show the following fact.…”
Section:    supporting
confidence: 56%
See 2 more Smart Citations
“…. } (they coincide with the polynomials defined in (1.8) in [26]). Taking into account (57) and (58), to prove Lemma 24 it is then sufficient to show the following fact.…”
Section:    supporting
confidence: 56%
“…Remark. We point out that the expression of α n and e (1) n taken from Corollary 2.1, equation (2.6) of [26].…”
Section:    mentioning
confidence: 99%
See 1 more Smart Citation
“…However, if A(x) can be expressed as a continued fraction, then there is a very nice formula. This is the case for g(x): Tamm [28] observed that g(x) has a nice continued fraction expression, which is a special case of Gauss's continued fraction. We introduce some notation to explain Tamm's approach.…”
Section: Hankel Determinants and Gauss's Continued Fractionmentioning
confidence: 94%
“…Using this theorem, Tamm[181, Theorem 3.1] observed that from Gauß' continued fraction for the ratio of two contiguous2 F 1 -series one can deduce several interesting binomial Hankel determinant evaluations, some of them had already been found earlier by Egecioglu, Redmond and Ryavec [53, Theorem 4] while working on polynomial Riemann hypotheses. Gessel and Xin [75] undertook a systematic analysis of this approach, and they arrived at a set of 18 Hankel determinant evaluations, which I list as (5.48)-(5.65) in the theorem below.…”
mentioning
confidence: 88%